Perumahan Tamarunang dalam memelihara drainase lingkungan - Ahmad Rifqi Asrib; Anas Arfandi (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Tamarunang is located approximately 10 km fromMakassar, and about 4 km from the border of Makassar Cityand Gowa Regency. As a developing area, TamarunangVillage is a reference for developers to build urbancommunities houses. The urbanization makes the growth ofhousing development more rapid. This has an impact onrainwater catchment areas turned into residential housing areas.The problems faced in this community partnership programsare: 1) the living area of partner 1 and 2 have poor drainageand reduced rain water catchment areas, 2) the impact of poordrainage causes water to overflow and pool on the public roadsand yard, 3) the garbage and sedimentation that accumulates inthe drainage causes clogged water flow, 4) due to thedevelopment of housing construction, causing the flowdirection and pattern of environmental drainage flow in thepartner area to be unclear. The method used in this communitypartnership program is mentoring method and participatoryrural approach (PRA) method. The mentoring method wascarried out to change the community's paradigm of thinking inhandling environmental drainage, increasing the community'sunderstanding of environmental cleanliness and structuring,and facilitating partners in making infiltration drainage, flowdirection maps, and environmental arrangement. The PRAmethod is carried out to arouse the partner's sense of belongingto the product to be developed, and the partner's sense ofresponsibility towards the products and environment thatsurrounds them. The main method adopted in this CommunityPartnership Program (PKM) activity is the time of presentationof counseling material, the method used is lecture, discussion,question and answer, and simulation, while during the practiceof making infiltration drainage, the method used isdemonstration. The results are the installation of biopori pipes,overflowing water and pooling on the road and the people'shome page has been reduced, and rainwater does not causestanding water on the road and downstream of the housingarea. And the construction of the drainage channel is intendedso that the drainage channel is not blocked again which cancause water to overflow into the highway.